KORELASI ANTARA BOBOT BADAN, LINGKAR SKROTUM, DAN VOLUME SEMEN KAMBING SABURAI DI WILAYAH SUMBER BIBIT KABUPATEN TANGGAMUS - Saputra, Andi Kurnia; Hamdani, M. Dima Iqbal; Suharyati, Sri; Hartono, Madi (Jurnal Riset dan Inovasi Peternakan, 2019)
This study aims to determined the correlation between body weight with scrotal circumference and volume of semen and scrotum circumference with volume of semen of Saburai Goat in the source breeding area, Tanggamus District. This research was observing 20 Saburai goat males in the breeding area by survey method. This research was conducted from 26 April to 30 July 2018. Research data used primary data and secondary data taken from direct observation in the field and recording of livestock from breeders' source areas. Data were analyzed by correlation analysis using SPSS software 16.0 version. The variables observed included body weight, scrotal circumference, and volume of semen. The results indicated that correlation between body weight and scrotum circumference 0,410; correlation between body weight and volume of semen 0,300; and correlation between scrotal circumference and volume of semen 0,148. Keywords: Saburai goat, body weight, scrotum circumference, and volume of semen.